ผลของแคลเซียมออกไซด์ต่อการเจริญเติบโตของต้นสับปะรดพันธุ์ภูเก็ต - กบค้างพลู แสงสุดา; ชุมภูคำ เจนจิรา; ฉัตรบรรยงค์ รัฐพล (Thai Journal of Science and Technology, 2018)
Abstract This experiment studied the effect of calcium oxide (CaO) on vegetative growth of ‘Phuket’ pineapple. One month old ‘Phuket’ pineapples were sprayed with calcium oxide solution (0, 150, 300, 450 and 600 mg·L-1) once a week for 8 weeks. The experiment was designed in Completely Randomized Design that composed of 5 treatments, 20 replications. The results showed that pineapple suckers sprayed with calcium oxide had better leaf length, canopy height, shoot fresh weight and shoot dry weight than those with non-treated calcium oxide. The application of CaO can be useful to improve the vegetative growth of ‘Phuket’ pineapple plant. Keywords: calcium; shoot growth; root formation